(untitled) (Hematology Meeting Reports, 2009)
Thalidomide represents a new milestone in the treatment of multiple myeloma and an opportunity to move away from cytotoxic agents toward an approach based on cellular signaling and cell-cell interactions. Alone, thalidomide produces several immunomodulatory effects that retard the progression of disease. In combination with conventional treatments, however, thalidomide produces a significant synergistic effect, resulting in improved treatment response and survival rates. The mechanism of action of thalidomide is complex. It impedes angiogenesis, alters myeloma plasma cell adhesion, increases the number of natural killer cells, and stimulates T-cell proliferation. Thalidomide also appears to produce direct anti-myeloma activity in vitro.